(untitled) (Proceedings of the International Conference on Public Health, 2021)
Since 2013, City of Denpasar government has adopted smoke-free law regarding smokefree areas including worship places. However, compliance with smoke-free law at worship places remains low. The implementation of the law faces several obstacles particularly at Hindu temples since it is mostly semi-opened spaces and high social acceptability of smoking where cigarette and smoking have been deeply engrained within social and religious life. Hence, this study aims to assess factors that associated with smoking behavior at worship places particularly at Hindu temple in Denpasar Bali Indonesia. This study was a cross-sectional study, conducted in the city of Denpasar, involving 192 samples which selected using multistage random sampling. The data was collected using a structured questionnaire then analyzed using path analysis. There were 12 factors analyzed such as past behavior of smoking, exposure to anti-smoking policies, nicotine dependence, knowledge and attitude regarding second-hand smoke, knowledge and attitude regarding implementation of smoke-free law, sociodemographic (age, education), social norms of smoking (descriptive and injunctive). Of the 11 factors, 5 factors had a significant effect on smoking behavior. Past behavior of smoking had a direct negative effect with a standardized coefficient (beta) -0.34 (p<0.01); followed by nicotine dependence which had an indirect negative effect (beta -0.07; p=0.01). Meanwhile, positive direct and indirect effects showed by descriptive norms (beta 0.14; p=0.04); injunctive norms (beta 0.15; p=0.02) and education (beta 0.14; p=0.03). Past behavior of smoking had the highest effect on smoking behavior in worship places. Hence, continuous education, socialization and improved supervision to the implementation of smoke-free law remain crucial. Moreover, social norm factors also need more attention, so that a culture-sensitive strategy could be considered